Dinâmicas de urbanização na hiperperiferia da metrópole de São Paulo: análise dos processos de expansão urbana e das situações de vulnerabilidade socioambiental em escala intraurbana - Alves, Humberto Prates da Fonseca [UNIFESP] (2010)
The objective of this article is to analyze, on an intraurban scale, the interrelations among processes of urban expansion and situations of socioenvironmental vulnerability in a hyperperipheral region of the São Paulo Metropolitan Region in recent years (2000 to 2006). This geographical region includes the district of Cidade Tiradentes and its surrounding area, located at the extreme eastern side of the municipality of São Paulo. The overall methodology of the study involves the mapping of the use of the soil and of the areas of urban expansion, using satellite images, as well as the identification and characterization of situations (areas) of socioenvironmental vulnerability. To this end, socioenvironmental indicators are constructed and analyzed based on census sectors from the Federal Census of 2000, including socioeconomic, demographic and environmental data. The results show a strong correlation between the processes of urban expansion and growth of substandard settlements and situations of socioenvironmental vulnerability in the hyperperipheral region of Cidade Tiradentes and its surrounding area. It was also seen that there are broad overlappings between social and environmental vulnerabilities, with strong concentration of social and environmental problems and risks in certain areas, as is the case of the census sectors of high socioenvironmental vulnerability in the Cidade Tiradentes region. These areas show irregularity in the use of the soil and widespread presence of substandard settlements such as shantytowns and irregular subdivision projects. There are also extremely critical socioeconomic conditions, with very low levels of income, formal education and sanitation.